Farey neighbors and hyperbolic Lorenz knots - Gomes, Paulo (2017)
Based on symbolic dynamics of Lorenz maps, we prove that, provided one conjecture due to Morton is true, then Lorenz knots associated to orbits of points in the renormalization intervals of Lorenz maps with reducible kneading invariant of type (X, Y)*S, where the sequences X and Y are Farey neighbors verifying some conditions, are hyperbolic.